1996
DOI: 10.1111/j.1469-8137.1996.tb04346.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the ribosomal internal transcribed spacers within and among isolates of Glomus mosseae and related mycorrhizal fungi

Abstract: SUMM.4RYThe internal transcribed spacer (ITS) region of the nuclear ribosomal RNA was amplified, cloned and sequenced from spores of five isolates of the arbuscular mycorrhizal fungus Glomus mosseae and one isolate each of G. fasciculatum, G. dimorphicum and G. coronatiim. The sequences comprised ITSl (113-121 base pairs), 5.SS rRNA gene (154 base pairs) and ITS2 (222-230 base pairs). The ITS sequences were at least 84% identical, but only distantly related to other published sequences. Their identification as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 25 publications
6
105
0
4
Order By: Relevance
“…Although it is not clear how frequently such an ITS polymorphism occurs in glomalean fungi, this phenomenon should be taken into account w-hen comparing ITS sequences from different isolates. It may prove difficult to distinguish the sequence divergence observed between species or isolates from the background of intraspore or intraisolate polymorphism (Lloyd-MacGilp et al, 1996).…”
Section: Its Polymorphismmentioning
confidence: 99%
“…Although it is not clear how frequently such an ITS polymorphism occurs in glomalean fungi, this phenomenon should be taken into account w-hen comparing ITS sequences from different isolates. It may prove difficult to distinguish the sequence divergence observed between species or isolates from the background of intraspore or intraisolate polymorphism (Lloyd-MacGilp et al, 1996).…”
Section: Its Polymorphismmentioning
confidence: 99%
“…Molecular analyses have revealed that a single AMF isolate or even individual spores may contain substantial heterogeneity among rRNA gene copies (2,12,31,33,34,40; for a recent review, see reference 41), which may be unevenly distributed in the heterokaryotic nuclei of AMF spores (31,54). Intraspecific rRNA heterogeneity seems to be a common phenomenon in AMF as well as in other groups of organisms, such as bacteria (1,37), plants (11), insects (52), and crustaceans (18).…”
mentioning
confidence: 99%
“…The high frequency of anastomosis formation and the establishment of protoplasmic continuity between fused hyphae suggested that the ability of self-compatible hyphae to recognize each other could represent a means for the exchange of genetic material, particularly if anastomoses occurred between hyphae derived from genetically different spores (15,26). Several studies have reported that individual spores of AM fungi, which are multinucleate (they may contain thousands of nuclei [7,53]) show a high level of genetic diversity in the internal transcribed spacer (ITS) region of the nuclear rRNA genes (3,28,30,42). Since AM fungi are considered clonal organisms (40), anastomoses between different germlings may represent a mechanism for the maintenance of genetic diversity in the absence of sexual recombination (6,41).…”
mentioning
confidence: 99%